Une stratégie sélective adoptée par des Africains dans le processus d’intégration en Chine. Le cas des commerçants africains à Yiwu - Can Cui (Cahiers d'Études du Religieux- Recherches Interdisciplinaires)
The city of Yiwu, a small city in China, is currently hosting the second largest African population in China for its dynamic commercial opportunities. Do they live apart from each other ? Is the interaction, if there is, restrained to business ? Are they excluded from the local society ? This article discovers and presents the structure of the social support that this population enjoys while presenting their relationships with their compatriots and the locals. There exists, as a matter of fact, a strong and influential network within the African community. Moreover, in order to assure their interest, they work actively with the Chinese, which could create a better image of themselves therefore leading to more potential benefits. However, such interactions are solely based on a practical interest, meaning that they are not truly nor fully integrated in the local society. In fact, their strategy is rather selective : integrate with certain people in certain context, normally related to business and distant themselves when the common interest disappears.